2015
DOI: 10.1016/j.berh.2015.04.022
|View full text |Cite
|
Sign up to set email alerts
|

Physical exercise as non-pharmacological treatment of chronic pain: Why and when

Abstract: Chronic pain broadly encompasses both objectively defined conditions and idiopathic conditions that lack physical findings. Despite variance in origin or pathogenesis, these conditions are similarly characterized by chronic pain, poor physical function, mobility limitations, depression, anxiety and sleep disturbance and are treated alone or in combination by pharmacologic and nonpharmacologic approaches, such as physical activity (aerobic conditioning, muscle strengthening, flexibility training and movement th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
270
2
15

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 385 publications
(295 citation statements)
references
References 89 publications
8
270
2
15
Order By: Relevance
“…The PA&E in this trial were based and modified from previous studies [193,216] which reported improvements in pain intensity and strength for women with pain in the neck-and shoulder muscles. PA&E in various combinations are often used for the treatment of chronic pain [3,[33][34][35][36][37][38][39]. However, despite the large amount of research on PA&E as treatment for chronic pain, there is still a lack of knowledge on physiological effects mechanisms behind the positive effects.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The PA&E in this trial were based and modified from previous studies [193,216] which reported improvements in pain intensity and strength for women with pain in the neck-and shoulder muscles. PA&E in various combinations are often used for the treatment of chronic pain [3,[33][34][35][36][37][38][39]. However, despite the large amount of research on PA&E as treatment for chronic pain, there is still a lack of knowledge on physiological effects mechanisms behind the positive effects.…”
Section: Discussionmentioning
confidence: 99%
“…However, in accordance with the suggestion that chronification of pain might be related to an imbalance between facilitating and inhibitory neurobiological systems [47,236], it is important to highlight the potential of PA&E to impact both ascending pain inducing activities as well as pain modulatory and descending activities in the nervous system. In future studies, the clinical effect on pain intensity and function as a result of different types of PA&E might not be of main interest to evaluate further, as several reviews [3,33,34,[36][37][38][39] and a metaanalyse [35] consistently shows that PA&E of different types are beneficial for chronic pain. To advance the research field, it might instead be interesting to add a focus on the physiological and neurobiological effect mechanisms associated to acute and long-term effects of PA&E in chronic pain.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations